Pengaruh Pendekatan Matematika Realistik Terhadap Prestasi dan Karakter Jujur Kelas III SDIT Al-Madinah Cibinong Bogor - Tyas Dian Lestari; Muhyani Muhyani; H.Mukhtar H.Mukhtar; Salati Asmahasanah (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2019)
This research is to know the effect of realistic mathematical approaches on learning achievement and honest character in second grade at Al-Madinah Cibinong Bogor Elementary School. This research was the quantitative research with types of quasi-experimental research, the selection of subjects in the quasi-experimental type of Non Equivalent Control Group Design was deliberately chosen by researchers. Using 3 variables, namely the independent variable (X) and the dependent variable (Y1, Y2). Data collection techniques using research instruments are observation, test and documentation. This research resulted in an average data post-test experimental class of 96,4 and the average post-test control class 87,4 so that the obtained -t count> -t table (-9,328> -7,211), it can be concluded that there are significant influenced of realistic mathematical approaches to achievement. Honest character observation data produced an experimental class average of 30,1, and the average after the application of the control class learning was 20.3 so that the obtained -t count> -t table (-42.121> -24.852), it can be concluded that there is significant effect of realistic mathematical approaches on learning achievement and honest character.